2019
DOI: 10.1111/jorc.12281
|View full text |Cite
|
Sign up to set email alerts
|

The “Mikidney” smartphone app pilot study: Empowering patients with Chronic Kidney Disease

Abstract: SUMMARY Background Successful management of chronic kidney disease (CKD) depends on patients′ self‐management efforts. Mobile health applications can empower patients with CKD to manage their own condition. We developed, with patient involvement, the MiKidney smartphone application. Aim Evaluate the MiKidney app as an aid to empowering patients with CKD to become more engaged in the management of their condition. Design Pilot single group pre‐ and post‐test intervention study. Setting Renal clinic of an urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(57 citation statements)
references
References 35 publications
(72 reference statements)
0
27
0
Order By: Relevance
“…Mobile health, also known as mHealth, has been defined by the World Health Organization as medical and public health practice through the use of mobile devices, such as mobile phones, patient monitoring devices, personal digital assistants, and other wireless devices (3). In interventional studies, mobile health has demonstrated improvement in patient-reported outcome measures (4), reduced use of health resources (5), and cost savings to health care services (6). In dialysis care, mobile health has been used to assist diet monitoring (7-10), treatment and symptom monitoring (11), and lifestyle management (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Mobile health, also known as mHealth, has been defined by the World Health Organization as medical and public health practice through the use of mobile devices, such as mobile phones, patient monitoring devices, personal digital assistants, and other wireless devices (3). In interventional studies, mobile health has demonstrated improvement in patient-reported outcome measures (4), reduced use of health resources (5), and cost savings to health care services (6). In dialysis care, mobile health has been used to assist diet monitoring (7-10), treatment and symptom monitoring (11), and lifestyle management (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Nine quantitative studies were considered: three RCTs; [5][6][7] one pilot single-group pre-and post-test intervention study; 8 one crosssectional survey; 9 and four observational studies. [10][11][12][13] Out of the entire corpus, three studies were conducted in Sweden [5][6][7] ; one in Ireland 8 ; one in the US; 9 one in Australia; 10 one in the Czech Republic; 11 one in Spain; 12 and one in Canada.…”
Section: Resultsmentioning
confidence: 99%
“…Nine quantitative studies were considered: three RCTs; [5][6][7] one pilot single-group pre-and post-test intervention study; 8 one crosssectional survey; 9 and four observational studies. [10][11][12][13] Out of the entire corpus, three studies were conducted in Sweden [5][6][7] ; one in Ireland 8 ; one in the US; 9 one in Australia; 10 one in the Czech Republic; 11 one in Spain; 12 and one in Canada. 13 In the studies examined, the following diseases were present: stress urinary incontinence (SUI); [5][6][7]9 chronic kidney disease (CKD); 8,10,13 and overactive bladder (OAB) 11,12 (See attached Tables 1, 2, 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations